2021
DOI: 10.1038/s41598-021-86665-6
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti miRNA-33 modulates permethrin induced toxicity by regulating VGSC transcripts

Abstract: Aedes aegypti is a major vector of Zika, dengue, and other arboviruses. Permethrin adulticidal spraying, which targets the voltage-gated sodium channel (VGSC), is commonly done to reduce local mosquito populations and protect humans from exposure to arbovirus pathogens transmitted by this dangerous pest. Permethrin resistance, however, is a growing problem and understanding its underlying molecular basis may identify avenues to combat it. We identified a single G:C polymorphism in pre-miR-33 that was genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Tevoltage-gated sodium channel (VGSC), a motoneuronal transport protein, is the target of all pyrethroids [94]. In addition, Kubik et al found miRNA-33 modulates permethrin induced toxicity by regulating VGSC transcripts [95].…”
Section: Pyrethroidmentioning
confidence: 99%
“…Tevoltage-gated sodium channel (VGSC), a motoneuronal transport protein, is the target of all pyrethroids [94]. In addition, Kubik et al found miRNA-33 modulates permethrin induced toxicity by regulating VGSC transcripts [95].…”
Section: Pyrethroidmentioning
confidence: 99%